Common and Specific Alterations of Amygdala Subregions in Major Depressive Disorder With and Without Anxiety: A Combined Structural and Resting-State Functional MRI Study - Li, Yao Yao; Ni, Xiao kang; You, Ya feng; Qing, Yan hua; Wang, Pei rong; Yao, Jia shu; Ren, Ke ming; Zhang, Lei; Liu, Zhi wei; Song, Tie jun; Wang, Jinhui; Zang, Yu-Feng; et al. (Frontiers in Human Neuroscience, 2021)
Anxious major depressive disorder is a common subtype of major depressive disorder; however, its unique neural mechanism is not well understood currently. Using multimodal MRI data, this study examined common and specific alterations of amygdala subregions between patients with and without anxiety. No alterations were observed in the gray matter volume or intra-region functional integration in either patient group. Compared with the controls, both patient groups showed decreased functional connectivity between the left superficial amygdala and the left putamen, and between the right superficial amygdala and the bilateral anterior cingulate cortex and medial orbitofrontal cortex, while only patients with anxiety exhibited decreased activity in the bilateral laterobasal and superficial amygdala. Moreover, the decreased activity correlated negatively with the Hamilton depression scale scores in the patients with anxiety. These findings provided insights into the pathophysiologic processes of anxious major depressive disorder and may help to develop new and effective treatment programs.